Monovalent protein-degraders – Insights and future perspectives. Issue 12 (15th June 2020) - Cornella-Taracido, Ivan; Garcia-Echeverria, Carlos
Graphical abstract: Abstract: The therapeutic potential of interfering with dysregulated proteins by inducing its selective degradation has been pursued using different mechanisms. In the present article, we review representative examples of monovalent protein-degraders that, contrary to the proteolysis targeting chimeras, achieve target degradation without displaying recognition motifs for the recruitment of E3 ubiquitin ligases. We also highlight new technologies and assays that may brought to bear on the discovery of common elements that could predict and enable the selective degradation of pathogenic targets by monovalent protein-degraders. The successful application of these methods would pave the way to the advancement of new drugs with unique efficacy and tolerability properties.